2020
DOI: 10.1001/jamanetworkopen.2020.23503
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologist to Patient Communication

Abstract: Key Points Question Do anesthesiologists or other anesthesia professionals engage in discussions with patients regarding decisions with implications beyond the operating room? Findings In this systematic review of the literature on communication between patients and anesthesia professionals, limited data were found on communication regarding perioperative decisions with implications that reach beyond the operating room. These data suggest that communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Despite a relatively equal contribution of psychiatrists and anesthesiologists to the decision-making (79% vs 81%), the majority of anesthesiologists in our sample did not provide specific answers to the questions of the respective domains (ie, decision-making and mitigating patient impact), instead indicating that those questions were not applicable to their expertise. Moreover, a relatively low response rate might reflect a tendency of anesthesiologists to overlook the critical impact of ECT disruption on morbidity and mortality of mood disorders, because this professional group is more likely to prioritize care for nonpsychiatric patient populations and not become involved in provider-patient communication for navigating postoperative care decisions 42 . Lastly, we identified the key issues surrounding ECT delivery during the first wave of COVID-19 based on individual experiences and opinions rather than standardized reports provided by institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a relatively equal contribution of psychiatrists and anesthesiologists to the decision-making (79% vs 81%), the majority of anesthesiologists in our sample did not provide specific answers to the questions of the respective domains (ie, decision-making and mitigating patient impact), instead indicating that those questions were not applicable to their expertise. Moreover, a relatively low response rate might reflect a tendency of anesthesiologists to overlook the critical impact of ECT disruption on morbidity and mortality of mood disorders, because this professional group is more likely to prioritize care for nonpsychiatric patient populations and not become involved in provider-patient communication for navigating postoperative care decisions 42 . Lastly, we identified the key issues surrounding ECT delivery during the first wave of COVID-19 based on individual experiences and opinions rather than standardized reports provided by institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a relatively low response rate might reflect a tendency of anesthesiologists to overlook the critical impact of ECT disruption on morbidity and mortality of mood disorders, because this professional group is more likely to prioritize care for nonpsychiatric patient populations and not become involved in provider-patient communication for navigating postoperative care decisions. 42 Lastly, we identified the key issues surrounding ECT delivery during the first wave of COVID-19 based on individual experiences and opinions rather than standardized reports provided by institutions. The results of this survey may thus have been skewed by possible biases due to a preferential response of those centers where the perceived impacts of the pandemic were the most evident.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding that surgery and life support are combined is also required. [24,25,27,29,33,35,43,45] In some cases, an extension in the duration of life support is presumed. After understanding this premise, the patient should discuss treatments that are unacceptable to the patient with the doctor.…”
Section: De Ning Attributesmentioning
confidence: 99%
“…For a patient to consider ACP, it is necessary to recognize the expected risks of surgery. This risk includes anesthesia and surgical complications [27,33,[35][36][37]41,43,45] as well as the possibility of rapid deterioration during treatment, [32,33,[35][36][37]40,41,43,47] the lack of time for contemplation in decision-making, [33,36,37,42] and the di culty of predicting the prognosis. [30,35,40,42,47] The assumption is that the patient is aware of the risk, needs to prepare for the worst that may occur after treatment, and needs anticipatory decisionmaking.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…Patients are unsure of the function of anesthesiologists, with only about half of the patients mentioning that "monitoring" is a duty of the anesthesiologists and only 25% were able to name any responsibilities the anesthesiologist has outside of the operating room [6]. Other studies have shown that patients who become critically ill following scheduled surgeries are unlikely to have talked to their anesthesiologist about their preferences when dealing with post-operative care decision making, like prolonged invasive ventilation or end-of-life care; instead, anesthesiologist-patient communication focuses on anesthetic planning, logistics, and risks vs. benefits talks [7].…”
Section: Introductionmentioning
confidence: 99%